The Imperative for Arabic Language Proficiency among Foreign Workers in Gulf Countries and Strategies for Enhancement l Ahammiyyatu Itqan al-Lughah al-‘Arabiyyah baina al-‘Ummal al-Ajnabi fi Duwali al-Khalij wa Istiratijiyyatu Ta’ziziha - El-Gammal, Mohammed; Sharaf, Najeem Adewale; Gunawan, Riski; Hidayatullah, Muhammad Subkhi (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
In both Eastern and Western societies, proficiency in the local language and an understanding of cultural nuances were traditionally considered essential prerequisites for employment. However, a marked deviation from this norm was evident in the Gulf states, where communication with foreign workers became sporadic and, in many cases, was limited to specific roles or enforced through punitive measures. This linguistic neglect perpetuated the erosion of Arab heritage, contributing to the gradual loss of identity. This research aimed to thoroughly analyze the importance of foreign workers in the Gulf countries mastering Arabic. It investigated the impact of neglecting this linguistic aspect and proposed viable solutions to encourage learning, thus contributing to the preservation and enhancement of cultural values, identity, and society in the Gulf region. Using a literature study methodology, the research drew on a variety of sources, including previous research, newspapers, expert studies, and reports. The findings of this research underscored the need for collaborative efforts among countries in the region, drawing inspiration from experiences in the East and West. An important solution identified was activating the principle of shared responsibility, which included the establishment of training centers for expatriates to acquire essential Arabic vocabulary. The implications of this research extended to the establishment of stronger communication links within the country, the creation of international bridges, and the opening of employment opportunities for Arabic language and literature experts.